2008
DOI: 10.3354/ab00024
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial symbionts and mineral deposits in the branchial chamber of the hydrothermal vent shrimp Rimicaris exoculata: relationship to moult cycle

Abstract: The shrimp Rimicaris exoculata is considered a primary consumer that dominates the fauna of most Mid-Atlantic Ridge hydrothermal ecosystems. The shrimps harbour in their gill chamber an important ectosymbiotic community of chemoautotrophic bacteria associated with iron oxide deposits. The settlement and development of this ectosymbiosis was investigated using microscopy techniques (light microscopy, LM; and scanning, transmission and environmental scanning electron microscopy: SEM and ESEM, respectively) for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(112 citation statements)
references
References 28 publications
6
104
1
Order By: Relevance
“…Finally, the view that bacterial products are assimilated across the shrimp integument rather than via the DT is strongly supported by: (1) the significant incorporation of both 14 C-acetate and 3 Hlysine after an incubation time as short as 1 h. This is insufficient for uptake by ingestion assimilation, which commonly takes several hours (ingestion assimilation of carbon from bicarbonate, for example, requires prior incorporation by the bacteria, followed by grazing of bacteria from the MP) (Chipps, 1998;Hoyt et al, 2000); (2) the high incorporation levels recorded in the gill chamber integument lining (OB, Gi), as opposed to (3) the much lower levels recorded in the DT (Figure 6). These results are in agreement with the view that the shrimps do not graze on their epibionts (Zbinden et al, 2004;Corbari et al, 2008b), but rather farm them (Segonzac et al, 1993;Polz and Cavanaugh, 1996), although they might also ingest some chimney bacteria along with sulphides (Van Dover et al, 1988;Segonzac, 1992). The low but nevertheless significant incorporation of 14 C from bicarbonate in the DT corroborates the data of Polz et al (1998), although they found higher rates than ours (upon incubating isolated gut segments).…”
Section: Bacteria-host Transferssupporting
confidence: 81%
See 4 more Smart Citations
“…Finally, the view that bacterial products are assimilated across the shrimp integument rather than via the DT is strongly supported by: (1) the significant incorporation of both 14 C-acetate and 3 Hlysine after an incubation time as short as 1 h. This is insufficient for uptake by ingestion assimilation, which commonly takes several hours (ingestion assimilation of carbon from bicarbonate, for example, requires prior incorporation by the bacteria, followed by grazing of bacteria from the MP) (Chipps, 1998;Hoyt et al, 2000); (2) the high incorporation levels recorded in the gill chamber integument lining (OB, Gi), as opposed to (3) the much lower levels recorded in the DT (Figure 6). These results are in agreement with the view that the shrimps do not graze on their epibionts (Zbinden et al, 2004;Corbari et al, 2008b), but rather farm them (Segonzac et al, 1993;Polz and Cavanaugh, 1996), although they might also ingest some chimney bacteria along with sulphides (Van Dover et al, 1988;Segonzac, 1992). The low but nevertheless significant incorporation of 14 C from bicarbonate in the DT corroborates the data of Polz et al (1998), although they found higher rates than ours (upon incubating isolated gut segments).…”
Section: Bacteria-host Transferssupporting
confidence: 81%
“…Several authors propose that organic nutrients might be transferred from epibionts to R. exoculata Zbinden et al, 2004;Corbari et al, 2008b). Others, arguing that the cuticle is impermeable, reject this hypothesis (Segonzac et al, 1993;Gebruk et al, 2000).…”
Section: Bacteria-host Transfersmentioning
confidence: 99%
See 3 more Smart Citations